An Efficient Synthesis of Fused Polycyclic Triazolo[4, 5-a]acridine Derivatives under Catalyst-Free Conditions with High Regioselectivity. (19th October 2016) - Jin, Rong-Zhang; Zhang, Yan; Li, Yu-Ling; Wang, Xiang-Shan
Abstract : An efficient synthesis of fused polycyclic 11-aryl-7, 8, 9, 11-tetrahydro-1 H -[1, 2, 3] triazolo[4, 5- a ]acridin-10(6 H )-one derivatives is described in EtOH with high regioselectivity. This new procedure includes a three-component reaction of benzaldehyde, 1 H -benzo[ d ] [1, 2, 3]triazol-5-amine and cyclohexane-1, 3-dione under catalyst-free conditions, and has the advantages of one-pot reaction, milder reaction conditions, high yields and high regioselectivity.